Evaluation of the Rock Uplift Pattern in the Central Yunnan Subblock, SE Tibetan Plateau: Based on the Bedrock Channel Profile - Yu, Liang; Dong, Youpu; Zhou, Weiwei; Zhang, Dongyue; Wang, Dan; Yu, Huayu; Ren, Yangyang; Li, Jiangtao (Frontiers in Earth Science, 2022)
The uplift pattern of the southeastern Tibetan Plateau is strongly related to the topographic evolution stemming from India-Eurasia collision. However, whether strain is localized along major faults that bound large tectonic blocks, or is accommodated across region has been strongly debated. In this study, we used stream power incision models to obtain the distribution pattern of the channel steepness indices to understand rock uplift pattern across the area, as increase channel steepness indices often correlate with rock uplift rates. In this study, the river longitudinal profiles were analyzed to obtain the distribution of channel steepness indices in the central Yunnan subblock. Results suggested that very weak correlations were found between steepness indices and lithology, precipitation, sediment flux, or channel concavity indices. Along the Xiaojiang strike-slip fault and the interior sublock, the uplift rate is slower, while the northern part has uplifted faster and is controlled by thrust fault systems. The Channel steepness increases gradually from south to north. Thus, the Ksn index distribution pattern within the central Yunnan subblock provides notable support for the argument for the thrusting transformation-limited extrusion model of the Tibetan Plateau.